2005
DOI: 10.2460/javma.2005.227.954
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Saccharomyces boulardii for treatment of horses with acute enterocolitis

Abstract: Administration of S. boulardii may help decrease the severity and duration of clinical signs in horses with acute enterocolitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 22 publications
3
55
1
6
Order By: Relevance
“…It proved the survival of S. boulardii in horses with gastrointestinal illness, "demonstrating that it can survive in the gastrointestinal tract of horses with intestinal pathology". However, in contrast to findings by Desrochers et al (2005), it did not prove that the treatment with S. boulardii had any impact on the duration of watery diarrhea.…”
Section: Clinical Studies In Adult Horsescontrasting
confidence: 52%
See 2 more Smart Citations
“…It proved the survival of S. boulardii in horses with gastrointestinal illness, "demonstrating that it can survive in the gastrointestinal tract of horses with intestinal pathology". However, in contrast to findings by Desrochers et al (2005), it did not prove that the treatment with S. boulardii had any impact on the duration of watery diarrhea.…”
Section: Clinical Studies In Adult Horsescontrasting
confidence: 52%
“…A study on Saccharomyces boulardii administration in horses with acute enterocolitis showed significant decrease in the duration of watery diarrhea and the duration of gastrointestinal illness (Desrochers et al, 2005). In this study 7 horses received the treatment and another 7 received placebo and no difference was found between these two groups in hospitalization duration, recurrence of diarrhea during hospitalization or disease outcome.…”
Section: Clinical Studies In Adult Horsesmentioning
confidence: 76%
See 1 more Smart Citation
“…Probiotics have been shown to be unable to colonize the gastrointestinal tract of horses and it is therefore unlikely that they can act beyond their period of administration 7, 10. The 1 week of treatment course chosen in previous studies therefore might not be sufficient to see an effect 3, 5, 9.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics exert their beneficial effect through several pathways, including production of antimicrobial compounds targeting intestinal pathogens and their toxins, as well as general immune stimulation and colonization resistance 6. Few studies in horses have been performed to date to evaluate the efficacy of probiotics in prevention or treatment of enteric disease 4, 7, 8. The 2 studies on probiotic use to prevent neonatal foal diarrhea failed to show a lack of significant effect of probiotic treatment 3, 9.…”
mentioning
confidence: 99%